2013
DOI: 10.1016/j.ijpe.2013.02.014
|View full text |Cite
|
Sign up to set email alerts
|

After-sales service competition in a supply chain: Does uncertainty affect the conflict between profit maximization and customer satisfaction?

Abstract: After-sales services are a key strategic tool in the durable consumer product market. They allow a manufacturer and a retailer to capture more sales and profit. Less obvious, however, is how the uncertainty of the customer's needs for after-sales services influences after-sales service decisions. As an extension of Kurata and Nam's (2010) work, in this paper we explore the effect of uncertainty on after-sales service decisions by comparing several information structures in a two-stage supply chain. The model p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 28 publications
2
41
0
1
Order By: Relevance
“…They find that the profit maximizing "optimal service plans" are different from the ones which most satisfy customers. Kurata and Nam (2013) further investigate the effect of uncertainty on after-sales service and find that information uncertainty can seriously harm the optimal after-sales service. They also explore a case under which efficient service increases the chance of accidental outperformance under uncertainty.…”
Section: Service Demand Managementmentioning
confidence: 99%
“…They find that the profit maximizing "optimal service plans" are different from the ones which most satisfy customers. Kurata and Nam (2013) further investigate the effect of uncertainty on after-sales service and find that information uncertainty can seriously harm the optimal after-sales service. They also explore a case under which efficient service increases the chance of accidental outperformance under uncertainty.…”
Section: Service Demand Managementmentioning
confidence: 99%
“…Dombrowski and Engel (2014) developed a method, which could help the stakeholders of the automotive aftermarket understand their existing strategy and detect alternative strategies to modify their existing strategy. Kurata and Nam (2013) investigated the impact of uncertainty on after-sales service decisions by comparing different information structures in a two-stage supply chain. The model showed that uncertainty may temporally reduce the discrepancy between customers' optimal service level and a company's service decisions according to profit maximization.…”
Section: Introductionmentioning
confidence: 99%
“…In [Kurata, Nam, 2013;Wei, Zhao, Li, 2015;Li, Mallik, Chhajed, 2012] incorporated the retailer into the after-sales service modeling. These authors developed the SG as a supply chain where both the retailer and the manufacturer can sell the after-sales services.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This game has been adapted to many situations, especially to extended warranty, maintenance outsourcing, maintenance service contracts and lease contracts [Ashgarizadeh, Murthy, 2000;Esmaeili, Gamchi, Asgharizadeh, 2014;Hamidi, Liao, Szidarovszky, 2016;Kurata, Nam, 2013;Li, Mallik, Chhajed, 2012;Murthy, Asgharizadeh, 1998;Murthy, Asgharizadeh, 1999;Murthy, Yeung, 1995;Wei, Zhao, Li, 2015].…”
mentioning
confidence: 99%